Ideal profile of essential amino acids for Nile tilapia (Oreochromis niloticus) in the finishing growth phase - Rodrigues, Andressa T. [UNESP]; Mansano, Cleber F. M.; Khan, Kifayat U. [UNESP]; Nascimento, Thiago M. T. [UNESP]; Boaratti, André Z. [UNESP]; Sakomura, Nilva K. [UNESP]; Fernandes, João B. K. [UNESP] (Hindawi, 2020)
This study aimed to estimate the ideal profile of essential amino acids (EAAs) for Nile tilapia (Oreochromis niloticus) in the finishing growth phase. A total of 264 fish (initial average weight of 625 g) were distributed among randomly arranged 33 fibre tanks of 1000-L water capacity each, connected to a water recirculation system. The 60-day experiment consisted of 11 treatments with three replicates each and fish were fed three times a day. The treatments consisted of a control diet (CD), 45% of which was composed of crystalline amino acids along with purified ingredients and the remaining 55% was contributed by the conventional ingredients meeting the nutritional requirements, and other 10 EAA-deficient test diets (DD) which were deficient from 33%–41% in each evaluated AA. The essential amino acid ratios were calculated from the relationship between body nitrogen retention and the amount of amino acid deleted from the test diet. This study found the following ideal profile of essential amino acids expressed in relation to lysine (100%); arginine (80.73%), phenylalanine (69.73%), histidine (34.15%), isoleucine (51.24%), leucine (66.01%), methionine (41.49%), threonine (88.96%), tryptophan (23.07%) and valine (72.63%).
Keywords: amino acid research; balanced diets; deletion method; fish nutrition; nitrogen retention